"...Making the most of what you have and getting the most out of what you make" : improvisation as a means of solving teaching challenges in Cameroon primary school - Safeh, Paschal (2019)
The main aim of the research is to investigate the challenges teachers face in the Southern Cameroon primary school classrooms, and to find out to what extent teachers employ improvisation as a means to addressing these challenges. The literature review affirms that teachers face situational challenges. These situational challenges arise daily in the classrooms. Hence, teachers must act in accordance to those challenges and requirements that arise from those different pedagogical circumstances. Ten government owned primary school teachers were involved in the research. The findings portray that Cameroon primary school teachers do face varied challenges such as lack of textbooks, over populated classrooms and the language of communication, time management and poor curriculum management. Improvisational practices do take place in Cameroon primary schools, albeit timidly. Findings reveal that the practice of improvisation is very common with long serving teachers than new recruits. Through improvisation, teachers are able to use what they have to attain desired results rather than sit and complain about their difficulties or wait for someone to do it for them. This study provides an overview of improvisation as a new concept in education, which if developed by teacher education shall become a professional skill. Such a skill shall be vital for harnessing appropriate teaching techniques towards attaining quality education in Cameroon.